2008
DOI: 10.1128/jcm.00367-08
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Molecular Characterization ofAcinetobacter baumanniiClinical Isolates from Nosocomial Outbreaks in Los Angeles County, California

Abstract: Multidrug-resistant Acinetobacter baumannii strains have increasingly resulted in nosocomial outbreaks worldwide, leaving limited options for treatment. To date, little has been reported on the antimicrobial susceptibilities and genomic profiles of A. baumannii strains from hospital outbreaks in the Greater Los Angeles area. In this study, we examined the susceptibilities and genetic profiles of 20 nonduplicate isolates of A. baumannii from nosocomial outbreaks in Los Angeles County (LAC) and determined their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 53 publications
10
110
1
2
Order By: Relevance
“…In this study, the antibiotic resistance rates of 103 Acinetobacter isolates to ciprofloxacin and levofloxacin were 74.7% and 33%, respectively. In contrast to ciprofloxacin, most of the isolates were susceptible to levofloxacin; this was also confirmed by the results (18). In contrast to the above-mentioned studies, Ribera et al observed that PAβN had no effect on MIC of ciprofloxacin (31); however, in general, in many studies such as the present one, the inhibitory effect of both compounds on the performance of efflux pumps has been observed (32).…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…In this study, the antibiotic resistance rates of 103 Acinetobacter isolates to ciprofloxacin and levofloxacin were 74.7% and 33%, respectively. In contrast to ciprofloxacin, most of the isolates were susceptible to levofloxacin; this was also confirmed by the results (18). In contrast to the above-mentioned studies, Ribera et al observed that PAβN had no effect on MIC of ciprofloxacin (31); however, in general, in many studies such as the present one, the inhibitory effect of both compounds on the performance of efflux pumps has been observed (32).…”
Section: Discussioncontrasting
confidence: 42%
“…The size of the culture medium was reduced and an inhibitor of the same amount was added, so that in each microplate, there were 48 µL of the adjusted Mueller-Hinton medium (Merck, Germany) and 2 µL of PAβN. After dilution of the antibiotic, the bacterial suspension was added by the same amount, ie, 50 µL (final volume of 100 µL), and all the remaining steps were conducted as MIC (18). As for the NMP inhibitor, based on the protocol, first 100 mg of the inhibitor was solved in 2 mL of DMSO, and then 2 mL of 0.25 molar HCL was added to it.…”
Section: Examining the Effects Of Paβn And Nmp Compounds On Minimum Imentioning
confidence: 99%
“…PCR assays as described by Valentine and colleagues [3] were used for the amplification of the QRDRs of the gyrA and parC genes. The gene fragments were sequenced and checked for specific amino acid changes.…”
Section: Analysis Of the Quinolone Resistance-determining Region (Qrdr)mentioning
confidence: 99%
“…Acinetobacter baumannii has been considered the paradigm of multiresistant bacteria because of emerging multi-drug resistance to various antimicrobial agents [2], notably mutations in gyrA and parC genes that confer fluoroquinolone resistance and activation of the aminoglycoside inactivating enzymes [2,3,4]. Betalactam antibiotics (mainly carbapenems) are now the first drug of choice to treat these microorganisms; however, in the last decade, resistance to carbapenems has appeared in hospitals worldwide owing to the production of beta-lactamases, changes in permeability, increase in efflux, and modification of the affinity of penicillin-binding proteins (PBPs) in these bacteria [2,3]. Transposable elements also play a major role in gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Another contains bile salts, ampicillin, cefsulodin, and vancomycin. In the Leeds medium formulation, ampicillin was removed and the concentrations of the other antibiotics were adjusted to optimise performance [5]. CHROMagar Acinetobacter® (CHROMagar, Paris, France) was recently developed as a selective agar for the rapid identification of A. baumannii.…”
Section: Introductionmentioning
confidence: 99%